Pengaruh Kualitas Produk, Kualitas Layanan, Dan Harga Terhadap Keputusan Pembelian Pada Toko Bantal Moker - Ely Rahmwati; Imam Badlowi; Toto Heru Dwihandako (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of product quality, service quality, and price on purchasing decisions at the Pillow Moker store through distributing online questionnaires to customers. The population in this study are customers who buy at the Moker Pillow shop with a sample of 98 respondents. The results of the respondent's questionnaire were analyzed by multiple linear regression through the SPSS 24 application. The results showed that the variable product quality, service quality, and price partially had a positive and significant effect on the purchase decision variable. While the variables of product quality, service quality, and price have a simultaneous effect on purchasing decisions. The results of the study show that product quality (X1) partially influences the decision to purchase pillow products at the Moker Pillow Shop with a t count of 6.953 > t table 1.660 with a significance level of 000. Service quality (X2) partially influences product purchase decisions Pillows at the Moker Pillow Shop with a t-count value of 7,993 > t-table 1,660 with a significance level of 000. Price (X3) partially influences the decision to buy Pillow products at the Moker Pillow Shop with a t-count value of 6,984 > t-table 1,660 with a significance level 000.